Enzymatic reaction of betulinic acid with acyl chloride: synthesis of anti-cancer compound / Yamin Yasin - Yasin, Yamin (Research Management Institute (RMI), 2011)
Betulinic acid, 3β-hydroxy-lup-20(29)-ene-28-oic acid (1), is a natural product which can be isolated from several genus of higher plants. Betulinic acid has been shown to exhibit a variety of biological activities. It was found to be an excellent anti-tumor agent due to its unique in vitro and in vivo cytotoxicity profile. Betulinic acid was also found to have activity and inhibition against human immunodeficiency virus (HIV) replication in lymphocyte cells, blockage of HIV-1 entry into cells and cytotoxicity against a variety of cultured human tumor cells (Bringmann et al., 1997).